(untitled) (Journal of Engineering, 2006)
In the present study, a general nonlinear one-dimensional finite element beam model is developed for the analysis of composite beams. The proposed model is based on the partial interaction theory of composite beams where the flexibility of shear connectors is allowed. By using a layered approach for the composite beam cross-section and including the material nonlinear behavior of concrete, steel, shear connector and reinforcing steel, the proposed method of analysis is capable of predicting the response of composite beams throughout the elastic, inelastic and ultimate load ranges in one complete analysis. Numerical case studies are presented to demonstrate the validity and applicability of the present method. The results are compared with experimental and analytical or numerical results obtained by other investigators. Also the results are compared with ANSYS package results. The maximum differences in deflection and slip for the examples considered are 12% and 14% respectively when compared with ANSYS and 5% and 11% when compared with experimental work. Accordingly, the proposed nonlinear finite element model represents an efficient and simple tool for the full range analysis of composite beams.